Community perceptions of climate change and vanability impacts in Oshana and Ohangwena Regions (Journal for Studies in Humanities and Social Sciences, 2014)
The links between climate change, social and economic development, health, and environmental sustainability have become a dominant and urgent global concern. Understanding community perceptions leads to successful adaptation to climate change. This paper analyses community perceptions of climate change in selected Namibian regions. The study applied the qualitative research approach using the focus group discussion method. The data collection was conducted within a Socio-economic and Gender Analysis framework. The study has revealed that the communities are aware that the climate is changing due to changes observed in the past three to four decades. However, the study concluded that the communities do not have an adaptive capacity to respond to catastrophic natural disaster events such as the recurrent floods of 2009, ww & 2011. The study recommends a programme on community awareness regarding climate variability and change and its implications. The government in collaboration with communities and other relevant stakeholders should set up a long-term adaptation strategy for Namibia.